Karakteristik pepton ikan kembung (Rastrelliger sp.) tidak layak konsumsi dan aplikasi pada pertumbuhan Wickerhamomyces anomalus: Characteristic of spoiled mackerel fish peptone (Rastrelliger sp.) and application in Wickerhamomyces anomalus growth - Manik, Btr Sri Syntia; Diapari, Didid; Nurhayati, Tati; Wijayanti, Indah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2024)
Selenium is a mineral element that acts as an antioxidant and affects enzyme formation, the immune system, and reproduction in livestock. Selenium yeast is an organic form of Se. The high availability of inedible mackerel can be utilized as a raw material for peptone in the growth medium of yeasts that produce organic Se. The objective of this study was to determine the characteristics of pepton derived from inedible mackerel as a growth medium for W. anomalus. Pepton was analyzed for amino acid composition using HPLC, solubility of pepton in water (gravimetric method), pepton yield, pH, proximate analysis, free α-amino nitrogen content, total nitrogen, AN/TN ratio, and salt content (Volhard method). Mackerel fish pepton has the following characteristics: protein content 75.5%, free α-amino nitrogen 1.9%, solubility 99.9%, total nitrogen 12.1%, salt content 7.9%, AN/TN ratio 16.2%, and pH 7.0. Mackerel fish pepton unfit for consumption applied to the growth medium of Wickerhamomyces anomalus as Se-Yeast has a higher growth rate compared to commercial pepton.